The Role of Opioid Use in Distinguishing between Suicidal Ideation and Attempts. Issue 6 (29th May 2019) - Anestis, Michael D.; Tull, Matthew T.; Butterworth, Sarah E.; Richmond, Julia R.; Houtsma, Claire; Forbes, Courtney N.; Gratz, Kim L.
Abstract : Objective: Opioid use disorders are associated with heightened suicidal ideation, suicide attempts, and suicide death. This study aimed to examine the extent to which opioid differentiates between those with suicide attempts from those with lifetime suicidal ideation but no history of attempt. Methods: Participants were drawn from the US National Guard and a residential substance use treatment facility. Multinomial logistic regression was utilized to determine the extent to which a lifetime history of nonmedical opioid use differentiated between (1) individuals with no lifetime history of suicidal ideation or attempt, (2) individuals with a history of suicidal ideation but no attempt, and (3) individuals with a history of at least one suicide attempt. Results: History of opioid use among National Guard personnel and opioid use disorders among substance‐dependent patients were associated with an increased likelihood of having at least one suicide attempt relative to both a history of suicidal ideation but no attempts and no history of ideation or attempts. Findings held when accounting for lifetime nonmedical use of other substances and the presence of other lifetime substance use disorders. Conclusions: Results highlight the importance of assessing for suicide risk among opioid users.